2011
DOI: 10.1016/j.freeradbiomed.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase and eNOS play differential roles in cytomegalovirus infection-induced microvascular dysfunction

Abstract: Primary cytomegalovirus (CMV) infection promotes oxidative stress and reduces nitric oxide (NO) bioavailability in endothelial cells. These events are among the earliest vascular responses to cardiovascular risk factors. We assessed the roles of NAD(P)H oxidase and NO bioavailability in microvascular responses to persistent CMV infection alone or with hypercholesterolemia. Wildtype (WT) or gp91phox (NAD(P)H oxidase subunit) knockout mice received mock-inoculum or 3×104PFU murine CMV (mCMV) IP 5wks before place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…Landmesser et al [ 27 ] reported that CMV infections can result in increased levels of oxidative stress and inflammation, which have been linked to endothelial damage in EH [ 28 ]. In an animal study, CMV infection was shown to reduce nitric oxide (NO) bioavailability in endothelial cells and activate nicotinamide adenine dinucleotide phosphate oxidase, which resulted in arteriolar dysfunction [ 29 ]. Recent evidence indicates that CMV infection impairs endothelial NO synthase (eNOS) function and causes endothelial damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Landmesser et al [ 27 ] reported that CMV infections can result in increased levels of oxidative stress and inflammation, which have been linked to endothelial damage in EH [ 28 ]. In an animal study, CMV infection was shown to reduce nitric oxide (NO) bioavailability in endothelial cells and activate nicotinamide adenine dinucleotide phosphate oxidase, which resulted in arteriolar dysfunction [ 29 ]. Recent evidence indicates that CMV infection impairs endothelial NO synthase (eNOS) function and causes endothelial damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is essential to compensate for vascular dysfunction in systemic (mesenteric) vascular beds that regulate blood pressure and cardiovascular function (36). The increase in ME-dependent vasodilation in mesenteric arteries from aged latently infected mice does not appear to be dependent on NOS or prostaglandin activity or an increase in smooth muscle sensitivity to NO, similar to findings in cremaster arteries from young persistently CMV-infected mice (31). It is therefore likely to be due to changes in other endothelium-derived hyperpolarizing factors that may contribute to ME-induced vasodilation (4).…”
Section: Discussionmentioning
confidence: 71%
“…and CMV infections (6,14,17,19,28,31) are associated with increased blood pressure, vascular stiffness, and vascular dysfunction. The systemic vasculature in aging may compensate for the combined insults of aging and infection with increased endothelium-dependent vasodilation, even in the presence of a latent, not active, mCMV infection (12).…”
Section: Discussionmentioning
confidence: 99%
“…Results from a population-based study evaluating cardiovascular risk factors and seropositivity to various pathogens [24] showed that antibody titers against CMV were not a marker for prevalence or incidence of atherosclerosis. However, evidence from animal studies points to an active role of CMV in cardiovascular disease including atherosclerosis [12, 2530]. It has been suggested that the contribution of CMV to atherosclerosis is through the initiation and sustainment of inflammatory processes [2628] induced by the virus.…”
Section: Discussionmentioning
confidence: 99%